Moderate nitrogen application improved salt tolerance by enhancing photosynthesis, antioxidants, and osmotic adjustment in rapeseed (Brassica napus L.) - Wang, Long; Zheng, Jingdong; Zhou, Guisheng; Li, Jing; Qian, Chen; Lin, Guobin; Li, Yiyang; Zuo, Qingsong (Frontiers in Plant Science, 2023)
Salt stress is a major adverse environmental factor limiting plant growth. Nitrogen (N) application is an effective strategy to alleviate the negative effects of salt stress on plants. To improve the knowledge of the mechanism of N application on alleviating salt stress on rapeseed seedlings, a pot experiment was conducted with four N application treatments (0, 0.1, 0.2, and 0.3 g N kg-1 soil, referred to as N0, N1, N2, and N3) and exposed to non-salt stress (0 g NaCl kg-1 soil, referred to as S0) and salt stress (3 g NaCl kg-1 soil, referred to as S1) conditions. The results indicated that in comparison with non-salt stress, salt stress increased the Na content (236.53%) and ROS production such as hydrogen peroxide (H2O2) (30.26%), resulting in cell membrane lipid peroxidation characterized by an increased content of malondialdehyde (MDA) (122.32%), and suppressed photosynthetic rate (15.59%), finally led to inhibited plant growth such as shorter plant height, thinner root neck, lower leaf area, and decreased dry weight. N application improved the plant growth, and the improvement by N application under salt stress was stronger than those under non-salt stress, suggesting that rapeseed seedlings exposed to salt stress are more sensitive to N application and require N to support their growth. Moreover, seedlings exposed to salt stress under N application showed lower ROS accumulation, increased photosynthesis, and higher antioxidants such as catalase (CAT), superoxide dismutase (SOD), glutathione reductase (GR), and ascorbic acid (AsA), and greater accumulation of osmotic substances including soluble protein, soluble sugar, and proline, as compared with seedlings without N application. Especially, the best improvement by N application under salt stress occurred at the N2 level, while too high N application would weaken the improvement due to inhibited N metabolism. In summary, this study suggests that moderate N application can improve photosynthesis, antioxidants, and osmoregulation to alleviate the adverse effects of salt stress in rapeseed seedlings.